Suicide-related behavior and firearm access among perpetrators of domestic violence subject to domestic violence protection orders - Dalve, Kimberly; Ellyson, Alice M.; Bowen, Deirdre; Kafka, Julie; Rhew, Isaac C.; Rivara, Frederick; Rowhani-Rahbar, Ali (Preventive medicine reports, 2024)
Perpetrators of domestic violence (DV) may be a population at elevated risk of suicide. Domestic violence protection orders (DVPOs) can include the removal of firearms from the individual subjected to the order (i.e., the respondent) to protect the victim-survivor. While removal of firearms in a DVPO is designed to protect the victim-survivor; it may also prevent suicide of the respondent by reducing access to lethal means. Therefore, we examined the association of respondent suicide-related behaviors with firearm possession and weapon use in DV among a sample of granted DVPO petitions in King County, Washington (WA), United States from 2014 to 2020 (n = 2,537). We compared prevalence ratios (PR) of respondent firearm possession and use of firearms or weapons to threaten or harm by suicide-related behavior. Overall, respondent suicide-related behavior was commonly reported by petitioners (46 %). Approximately 30 % of respondents possessed firearms. This was similar between respondents with and without a history of suicide-related behavior (PR: 1.03; 95 % CI: 0.91–1.17). Respondents with a history of suicide-related behavior were 1.33 times more likely to have used firearms or weapons to threaten/harm in DV compared to those without a history of suicide-related behavior (44.1 % vs. 33.8 %; 95 % CI: 1.20–1.47). In conclusion, both firearm possession and suicide-related behaviors were common among DVPO respondents. History of suicide-related behavior may be a marker for firearm-related harm to the victim-survivor. Evaluations of DVPO firearm dispossession should consider both firearm-related injury of the victim-survivor and suicide of the respondent.